The lawman's promise - Morgan, Alexis (Harlequin heartwarming, 2023)
"Museum curator Shelby Michaels seems to be the only woman in Dunbar not chasing after the new police chief, Cade Peters. When a stranger lays claim to the town's famous gold nugget, Shelby helps Cade find the truth. Because if the town loses this precious connection to its past, Cade's job here is done. Can Shelby stop herself from falling for a man who may not stick around?" - back cover.